Can product-information disclosure increase Chinese consumer's willingness to pay for GM foods? The case of Fad-3 GM lamb. Issue 3 (4th September 2017) - Chen, Qihui; Liu, Gaoshuai; Liu, Yumei
Abstract : Purpose: The purpose of this paper is to examine Chinese consumers' level of perception of genetically modified (GM) foods and the determinants of their willingness to pay (WTP) for Fad-3 GM lamb, a newly developed GM product. Design/methodology/approach: Based on a randomized choice experiment involving 576 consumers in Beijing, the authors adopt a double-bounded contingent valuation method to estimate consumers' WTP for Fad-3 GM lamb, as well as the causal impact of (randomized) product-information disclosure on it. Findings: The econometric result indicates that the randomly disclosed product information describing details about Fad-3 GM lamb, the potential risks associated with the consumption of it, and the related governmental regulation policies raised consumers' WTP by 6.2 yuan per Jin (or US$2/kilogram). Originality/value: This paper provides new experimental evidence of the effect of product-information disclosure on consumers' WTP for a newly developed GM food product.